A Study of Nanoclay Reinforcement of Biocomposites Made by Liquid Composite Molding. (17th July 2011) - Bensadoun, Farida; Kchit, Nadir; Billotte, Catherine; Bickerton, Simon; Trochu, François; Ruiz, Edu
Abstract : Liquid composite molding (LCM) processes are widely used to manufacture composite parts for the automotive industry. An appropriate selection of the materials and proper optimization of the manufacturing parameters are keys to produce parts with improved mechanical properties. This paper reports on a study of biobased composites reinforced with nanoclay particles. A soy-based unsaturated polyester resin was used as synthetic matrix, and glass and flax fiber fabrics were used as reinforcement. This paper aims to improve mechanical and flammability properties of reinforced composites by introducing nanoclay particles in the unsaturated polyester resin. Four different mixing techniques were investigated to improve the dispersion of nanoclay particles in the bioresin in order to obtain intercalated or exfoliated structures. An experimental study was carried out to define the adequate parameter combinations between vacuum pressure, filling time, and resin viscosity. Two manufacturing methods were investigated and compared: RTM and SCRIMP. Mechanical properties, such as flexural modulus and ultimate strength, were evaluated and compared for conventional glass fiber composites (GFC) and flax fiber biocomposites (GFBiores-C). Finally, smoke density analysis was performed to demonstrate the effects and advantages of using an environment-friendly resin combined with nanoclay particles.